Georgia : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Performance Criterion and Conversion of an Indicative Target into a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses key findings of the Second Review Under the Poverty Reduction and Growth Facility (PRGF) for Georgia. All quantitative performance criteria (PCs) for end-December 2004 were met, but the indicative target on reserve money growth was exceeded, mainly because of large unsterilized intervention in the foreign exchange market. The structural reform agenda focuses on consolidating the fiscal gains, removing key obstacles to growth, and enhancing social protection and the provision of basic services.